Repolarization heterogeneity within the myocardial infarction border zone correlates with variability of myocyte remodeling. (14th October 2021) - Vermoortele, D; Amoni, M; Ingelaere, S; Holemans, P; Willems, R; Sipido, K; Claus, P
Abstract: Background: Myocardial infarction (MI) results in a regional scar, with a border zone (BZ) of surviving myocytes interspersed with fibrosis providing an anatomical substrate for re-entry. Heterogeneous repolarization within the BZ may add a functional component aggravating re-entrant arrhythmias. Purpose: We studied BZ heterogeneity and developed novel methodology for high resolution mapping of local in vivo activation-repolarization intervals (ARI) within the BZ and for studying the relation to cellular action potential (AP) profiles of cells isolated from the BZ. Methods: Anterior-septal myocardial infarction was induced in 5 domestic pigs by 120-minute occlusion of the left anterior descending artery followed by reperfusion (18.9±4.7% of the left ventricle). After 1-month, electro-anatomical mapping was performed. Contact mapping was used to define the BZ (bipolar voltage 0.5–1.5mV). A non-contact recording of a 64-electrode array was translated to 2048 non-contact electrograms distributed over the LV. The non-contact electrograms were processed to determine the ARIs using a custom-made algorithm, validated against monophasic action potential recordings. After 2–4 days recovery, single cardiomyocytes were enzymatically isolated from the anterior-septal BZs and remote regions. Cardiomyocytes were field stimulated at 1Hz at 37°C and cellular AP duration (APD) was optically recorded (fluorescent voltage-sensitive dye Di-8-Annepps). Results: In vivo, regional ARIs tended to be longer in the BZs than remote. ARI heterogeneity, quantified as the standard deviation of ARIs in a neighborhood of 1cm radius, was increased in the BZ (anterior BZ: 3.4±1.0 ms, P=0.052, septal BZ: 3.6±1.7 ms, P=0.027 vs remote: 2.0±0.5 ms). Cellular APD was measured in large population samples (>100 cells per region in each pig) and was longer in BZ myocytes compared to the remote region. Cellular APD heterogeneity, measured as the standard deviation within cell population samples pooled by region per animal, was increased in the BZ (anterior BZ: 105.9±17.0 ms, P=0.0010; septal BZ: 98.1±20.8 ms, P=0.0127 vs remote: 73.9±8.6 ms). Cell APD correlated to in vivo ARI (R 2 =0.34, P=0.021) and cellular heterogeneity correlated strongly with in vivo heterogeneity (R 2 =0.67, P=0.002). Conclusion: In the BZ of MI, in vivo regional heterogeneity adds a functional substrate for re-entry that may result from heterogeneous cellular remodeling and increased cell-cell APD variability. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): KU Leuven BOF-C1 "Blood pressure induced premature ventricular beats as triggers for ventricular arrhythmia in ischemic cardiomyopathy"